(untitled) (IJM: Journal of Multidisiplinary, 2026)
Work discipline is one of the key factors in enhancing employee performance and productivity, particularly in large-scale organizations such as PT PLN (Persero) UP3 Madiun. This independent work report aims to analyze the implementation of work discipline through attendance and punctuality, compliance with Standard Operating Procedures (SOP) and Occupational Health and Safety (OHS) regulations, as well as the utilization of digital technology to support work discipline. The methods employed include direct observation, organizational data collection, and documentation during the activity period. The results indicate that the implementation of digital attendance systems, corporate AMS, and the Vendor Invoicing Portal effectively enhances discipline, administrative efficiency, and the accuracy and transparency of work processes. Compliance with SOP and OHS contributes to improving workplace safety, task execution effectiveness, and overall employee performance quality. The synergy between work discipline, adherence to SOP and OHS, and the support of digital technology has been proven to enhance employee performance and support the achievement of organizational goals effectively and sustainably.